Dosen Otoritatif: Analisis Persepsi Mahasiswa STIE Balikpapan - Puspita, Ephine Khaylilla; Tsalisa, Syafarani; Pranata, Raynaldi; Anhar (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to investigate student’s perceptions of authoritative teachers, commonly referred to as